Nilai-Nilai Islam dalam Rantai Produksi dan Pemasaran Online shop Elena Collection - Dea Ayuni; Nurul Wulandari Putri (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This research aims to identify the application of Islamic values in the production and marketing chain of Online Shop Elena Collection, an online shop that sells bags and clothing. The main focus of this research is the application of the principles of honesty, justice, sustainability and Islamic-based promotional ethics. The research method used is descriptive qualitative with interviews, observation and document analysis. The research results show that the Elena Collection has implemented Islamic values, especially in price transparency, use of halal materials, and promotions that comply with sharia. However, challenges remain, such as ensuring halal supply chains and balancing market demands with sharia principles.